A Bottom-Up Account of State Supreme Court Opinion Writing. (2nd April 2016) - Savchak, Elisha Carol; Bowie, Jennifer Barnes
Abstract: This research addresses the central product of judicial work, written opinions. We investigate whether lower court judges are in the position to influence the interpretation of law at higher courts through their own opinions. An examination of 847 state supreme court cases in 1997 shows that the writings of lower court judges do serve as a foundational basis in a bottom-up method of opinion writing, which is conditioned by career factors, including previous jobs and being appointed to the state supreme court, and the judicial workload. This research expands our understanding of opinion writing by shedding light on the differences and similarities in the ingredients of judicial opinions at different court levels and corroborates the growing importance and effectiveness of lower court judges in the creation of law.